2006
DOI: 10.1364/ol.31.001636
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed digital holography system recording ultrafast process of the femtosecond order

Abstract: We report, for the first time to our knowledge, a pulsed digital microholographic system with spatial angular multiplexing for recording the ultrafast process of the femtosecond order. The optimized design of the two sets of subpulse-train generators in this system makes it possible to implement a digital holographic recording with spatial angular multiplexing of a frame interval of the femtosecond order, while keeping the incident angle of the object beams unchanged. Three pairs of amplitude and phase images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Balciunas et al [22] presented an off-axis DH using a MachZehnder interferometer for characterization of ultrafast phenomena in water. Wang et al [23] reported a spatial angular multiplexing DH. However, these previous works only studied the transient changes in transparent materials, such as air or water.…”
Section: Introductionmentioning
confidence: 99%
“…Balciunas et al [22] presented an off-axis DH using a MachZehnder interferometer for characterization of ultrafast phenomena in water. Wang et al [23] reported a spatial angular multiplexing DH. However, these previous works only studied the transient changes in transparent materials, such as air or water.…”
Section: Introductionmentioning
confidence: 99%
“…The IDIA technique is based on optically multiplexing [7][8][9][10][11][12][13] two FOVs of the sample and interfering them with a reference beam in an off-axis geometry, such that the off-axis interferences from the two FOVs create straight parallel fringes with directions orthogonal to each other, and the two FOVs of the sample are thus recorded simultaneously using a single camera exposure. In the case that the same reference beam is used for the two FOVs of the sample, the digital camera at the output of the interferometric system records three separable off-axis interferences: two between the reference beam and each of the sample beams and one between the two sample beams.…”
Section: Methodsmentioning
confidence: 99%
“…Multiplexing several off-axis interferograms into a single interferogram and reconstructing the data encoded into each of them have already been shown to be feasible. 20 This feature has been used in the past for other applications, which include solving the phase unwrapping problem, 9,21 recording ultrafast events using suitable temporal encoding, [22][23][24] and obtaining super-resolution capabilities by synthetically increasing the numerical aperture (NA) of the imaging system. [25][26][27] Although the IDIA principle can be implemented in various holographic and interferometric imaging systems, we implemented this technique by modifying the compact and portable interferometric module recently developed in our group, 6,7 which can be connected directly to the digital camera to turn it into a powerful off-axis interferometric camera with a wider FOV.…”
Section: Introductionmentioning
confidence: 99%